Efektifitas Penyuluhan Kesehatan Tentang SADARI dengan Metode Diskusi Kelompok dan Metode Demonstrasi terhadap Perilaku WUS dalam Melakukan SADARI - Ucik Masturo; Kholisotin Kholisotin; Y. D. Agustin (Citra Delima Scientific journal of Citra Internasional Institute, 2020)
Women all over the world are at risk of developing cancer, so early detection is necessary SADARI. The aim of the study was to determine the effectiveness of health education about BSE using discussion methods and demonstration methods on behavior in Ambulu Village, Wringin District, Bondowoso District. The research design used the pre-eksperimental two-group pretest-posttest design with a total sample of 84 people with purposive sampling technique. Then analyzed by Mann Whitney and Wilcoxon statistical tests with a significance level of α ≤ 0.05 to determine the comparison between two different groups. The results showed that there were differences in health education with methods of discussion and demonstration of behavior. The conclusion that the demonstration method is more effective than the group discussion method in improving behavior Keywords : Extension, Group Discussion, Demonstration, SADARI